IMPLEMENTASI MODEL PEMASARAN DI MASA PANDEMI COVID-19 BAGI UMKM TANAMAN HIAS KEC. CIBEUNYING KIDUL KOTA BANDUNG - Supriyanto, Dodi; Hasanah, Nurul; Prasetyo, Muhammad Pandu (Lembaga Pengabdian Masyarakat Universitas Swadaya Gunung Jati, 2021)
The ornamental plant trader was established in 2016 having his address at Jalan Canal Citamiang, Cibeunying Kidul District, Bandung City 40121. The land used for ornamental plants is owned by the West Java Provincial Government, which is managed by the Infantry Weaponry Center. The marketing pattern is still conservative. This means that ornamental plant traders are more waiting for the arrival of consumers to the place of sale compared to making sales pro-actively coming to consumers. The implementation method in carrying out community service includes, 1) Conducting a preliminary survey to find out the condition of ornamental plant traders in general such as facilities and environmental conditions as well as those specifically related to the marketing process that is currently running. 2) Compile an improvement plan from the results of a preliminary survey that has been carried out and communicate to the owners of ornamental plants about the program to be implemented accompanied by a schedule of activities. This business, if managed properly and with a marketing pattern using social media, will generate greater profits. So that this business is not only a source of livelihood, but also can be a profitable business in the future.